Negative 11C-choline PET/computed tomography imaging in restaging of patients with prostate cancer with serum prostate-specific antigen values >20 ng/mL. Issue 11 (November 2020) - Telo, Silvi; Fanti, Stefano; Nanni, Cristina; Lambertini, Alessandro; Picchio, Maria; Gianolli, Luigi; Schiavina, Riccardo; Bianchi, Lorenzo; Briganti, Alberto; Mapelli, Paola; Castellucci, Paolo; Farolfi, Andrea
Abstract : Objective: Several studies have reported about the performance of 11 C-choline-PET/computed tomography (CT) (choline) in patients with biochemical recurrent (BCR) prostate cancer, but there is a lack of information regarding negative choline in the same clinical setting. Our aim was to retrospectively analyse negative choline in a cohort of BCR-patients with high prostate-specific antigen (PSA). Methods and Results: We retrospectively analysed all choline-scans performed at two high-volume imaging centres between 2005 and 2018, selecting those of interest according to the following inclusion criteria: (1) proven prostate cancer treated either with radical prostatectomy or primary external beam radiation therapy (EBRT), (2) BCR after radical prostatectomy or EBRT, (3) PSA serum values >20 ng/mL at the time of scan and (4) scan reported as negative for active disease. Overall, among 5792 scans performed for BCR-prostate cancer, 14 matched the inclusion criteria and were classified as follows: 5/14(36%) inaccurate reports, 3/14(21%) questionable underestimation of positive findings, originally described as unclear, 6/14(43%) negatives. Choline showed a high detection rate in BCR-prostate cancer patients with PSA >20 ng/mL. Conclusions: Although negative reports can be found in this clinical setting, in our review various disease-relevant findings were identified in more than half of the cases originally reported as negative warranting a double reading in such cases to avoid false-negative reports.